Very strong but exchangeable organic ligand of cobalt in the marginal sea. Issue 6 (14th April 2022) - Wong, Kuo Hong; Xu, Jiarui; Kondo, Yoshiko; Takeda, Shigenobu; Mashio, Asami S.; Hasegawa, Hiroshi; Obata, Hajime
Abstract: Cobalt (Co) is an important micronutrient for phytoplankton and its chemical speciation in the ocean is dominated by organic complexation. However, determination of the chemical speciation parameters of dissolved Co (dCo) in seawater is difficult because the ligands have conditional stability constants ( K ′) higher than those detectable by current forward titration methods. Furthermore, forward titration is not ideal when the ligand concentration is less than the dCo concentration in natural seawater, which is a probable scenario because excess ligands will bind more strongly to nickel instead. In this study, we successfully determined the concentrations and K ′ of the dCo‐binding organic ligands in East China Sea using the reverse titration method. Our results indicate that organic complexes of dCo in the East China Sea are very strong but are kinetically exchangeable at high detection windows. Log K ′ values of the ligands were between 16.6 and 17.1 in the Kuroshio waters and ranged from 19.7 to 20.9 in coastal waters. These ligands might be phytoplankton exudates or degradation products of cobalamin. Our findings suggest that an inert dCo fraction may be significant in coastal regions with high primary productivity. These inert dCo complexes were not detected within our detection window, which may lead to overestimation of the titration results.